Public agricultural research in Latin America and the Caribbean: Investment and capacity trends - Stads, Gert-Jan; Beintema, Nienke M. (International Food Policy Research Institute, 2009)
The countries of Latin America and Caribbean (LAC) represent a wealth of natural resources; the world’s greatest agrobiodiversity; and immense economic, social, and environmental diversity. As an example, the region is home to Brazil—the world’s fifth-largest country in terms of both area and population—yet it also comprises numerous Caribbean island nations populated by fewer than 100,000 people. Nonetheless, LAC countries exhibit much commonality, including significant urban populations, high ethnic diversity, and increasing inequality and poverty. Another shared factor is that many LAC countries have reformed or are in the process of reforming their economies through structural adjustment programs. Agriculture faces many challenges in LAC, especially in the context of development. Rising food prices are a growing policy concern for both low- and middle-income countries, and, whereas the region as a whole is a net food exporter, poor consumers suffer the negative impacts of food-price inflation on their incomes and thus on their health and nutrition. In addition, international value chains and supermarkets are transforming domestic food markets, thereby posing serious challenges to smallholders in their ability to remain competitive. As commercial agriculture expands, the agricultural labor market and rural nonfarm economy become vital if resulting productivity gains are to have a beneficial effect on rural poverty.